Environmental and provenance change since MIS 2 recorded by two sediment cores in the central North Jiangsu Plain, East China - Chen, Yingying; Xia, Fei; Zhang, Zhenke; Xu, Qinmian; Gui, Feng (Frontiers in Earth Science, 2023)
Identification of sediment origins of the central North Jiangsu Plain since the Last Glacial Maximum (LGM) were uncovered, based on the lithology, accelerator mass spectrometry (AMS) 14C dating, macrofossils and foraminifera, grain-size and geochemical analyses of Core M and Core Y in the northern part of the Yangtze River delta. Fe/Al-Ti/Al, Fe/Al-K/Na ratios and the calculated results of provenance index (PI) using a two-end-member mixing model indicate alternating influence of the Yellow River and the Yangtze River on the North Jiangsu Plain since the LGM. River floodplain deposits were developed during the LGM (25-15 ka BP) in the study area, the Yangtze River sediments dominated over the area during this period. The south region of the study area was lack of the early PG sediments, and coastal marsh deposit was developed during middle-late period of the PG period, elemental ratios and PI values (averaging 0.64) revealed that the PG sediments still received the Yangtze River sediments. Nevertheless, coastal marsh and shallow bay deposits were developed in the north region of the study area during the early post glacial period to the post-glacial transgression maximum ( 7000 a BP), and received the Yellow River sediments supply which might be transported from previously deposited sediments by strong tidal current and intense wave to this area, or a reflect of southward shift of the Yellow River during this period; after the post-glacial transgression maximum, the sea level tend to be stable and the paleo-coastline advanced to east of the study area, coastal marsh deposit was developed and it was still controlled by the Yellow River-derived sediments. Changes of sediment supplies and sedimentary environment change in the middle part of the North Jiangsu Plain were controlled primarily by sea-level fluctuations, regional geomorphic pattern, shift of the rivers, etc.